Residential Real Estate Market Characteristics and Mortgage Origination in Emerging Economies: The Case of Ghana - Akinsomi, Omokolade; Anim-Odame, Wilfred; Owusu Junior, Peterson (Journal of African Real Estate Research, 2025)
This study analyses the relationship between mortgage origination and residential real estate property characteristics in Ghana. Using transaction-based data on 1476 mortgages from 2008 to 2016, we apply the hedonic pricing model and multivariate regression to establish the role of structural property characteristics and residential real estate sub-markets in determining mortgage origination, separated into loan amount and loan-to-value (LTV) ratio. Further, the risk of default in the mortgages is estimated as an additional risk assessment tool for lenders. The findings reveal that residential sub-markets are important variables to consider when mortgages are originated. In Ghana, properties in Upmarket, Emerging upmarket, and Middle-income sub-markets tend to attract lower loan values in comparison to properties in Gated communities, primarily due to their neighbourhood characteristics. In addition, properties in emerging, upmarket, and middle-income sub-markets attract higher LTV ratios. It was revealed that in upmarket areas, the number of bedrooms, detached, and outhouses does not contribute to determining the risk of default in mortgages. We also find that the risk of default by mortgage borrowers is negligible, indicating that lenders can safely expand their customer base. The findings offer rare insights into the emerging mortgage market in Africa for both policy and investment purposes.